Elaboration of sausage using minced fish of Nile tilapia filleting waste - Oliveira Filho, Paulo Roberto Campagnoli de [UNESP]; Maria Netto, Flavia; Ramos, Kazumi Kawazaki; Trindade, Marco Antônio; Viegas, Elisabete Maria Macedo [UNESP] (Brazilian Archives of Biology and Technology, 2010)
O objetivo deste estudo foi avaliar a inclusão de carne mecanicamente separada (CMS) (0, 20, 40, 60, 80 e 100%), obtido de resíduos de filetagem de tilápias do Nilo, em salsichas e determinar suas propriedades físico-químicas, nutricionais e sensoriais. As salsichas apresentaram diminuição de proteína e aumento de lipídeos com a inclusão de CMS. A qualidade nutricional dos produtos foi alta, com digestibilidade acima de 85%. Os parâmetros de textura e cor instrumental amarela (b*) diminuíram com inclusão crescente de CMS. A avaliação sensorial da cor mostrou que o nível máximo de inclusão de CMS não foi bem aceito pelos provadores. As salsichas com melhor aceitação do atributo sabor foram aquelas com 60% de CMS. Os resultados demonstraram a boa qualidade nutricional das salsichas utilizando CMS de resíduos de filetagem de tilápias do Nilo e de acordo com avaliação sensorial, a porcentagem máxima de inclusão é de 60%.

The objective of this study was to evaluate the inclusion of minced fish (MF) (0, 20, 40, 60, 80 and 100%), obtained from Nile tilapia filleting waste, in sausage and determine their physicochemical, nutritional and sensory properties. The sausages showed a decrease in protein and increase in fat content with increasing inclusion of MF. The nutritional quality of the products was high, with digestibility over 85%. The parameters of texture instrumental and yellow color (b*) decreased with the increasing inclusion of MF. The sensory evaluation of the color showed that the maximum level of inclusion of MF was not well accepted by the panelists. The sausage with the best acceptance for the flavor attribute was those with 60% of MF. The results showed good nutritional quality of sausages utilizing MF of Nile tilapia filleting waste and according to the sensory evaluation, the maximum level of inclusion should not exceed 60%.
Keywords: Oreochromis niloticus; sausage; nutritional quality; minced fish; sensory acceptance; texture